2020
DOI: 10.3390/molecules25081824
|View full text |Cite
|
Sign up to set email alerts
|

Development and Study of Semi-Solid Preparations Containing the Model Substance Corticotropin (ACTH): Convenience Application in Neurodegenerative Diseases

Abstract: Corticotropin (ACTH, previously an adrenocorticotropic hormone) is used in the diagnosis and treatment of pituitary gland disorders, adrenal cortex disorders, and other diseases, including autoimmune polymyositis, systemic lupus erythematosus, rheumatoid arthritis, Crohn’s disease, and ulcerative colitis. So far, the ointment dosage form containing ACTH for use on the skin is unknown. Therefore, it seems appropriate to develop a semi-solid formulation with corticotropin. Emulsion ointments were prepared using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The results of the release test showed that ACTH is released the fastest from the preparation with the lowest concentration. Higher concentration may ensure prolonged release process [24]. A very short time of hormone release from the all formulations was also found.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The results of the release test showed that ACTH is released the fastest from the preparation with the lowest concentration. Higher concentration may ensure prolonged release process [24]. A very short time of hormone release from the all formulations was also found.…”
Section: Introductionmentioning
confidence: 79%
“…From these preparation corticotropin was released the fastest from the ointment of the lowest concentration; with increasing concentration, the rate of ACTH release decreased. The highest correlation coefficient in determining kinetic models was recorded for the Higuchi model [24]. On the other hand, from all formulations based on glycerol ointment ACTH was released longer than 150 min and its amount increased with increasing concentration in the ointment.…”
Section: Kinetics Calculationsmentioning
confidence: 93%
See 1 more Smart Citation
“…F2 was the maximum force value in the second cycle. Hardness corresponded to the maximum force value in the first pressing section [ 34 , 35 , 36 ]. The measurements were carried out at 25 ± 1 °C and 32 ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of hormone released per unit time was calculated and release profiles were plotted. The method of corticotropin determination was described by Siemiradzka et al [11,12]. Measurements were made using a UV-VIS Cecil CE 3021 spectrophotometer (Cecil Instruments Limited, Cambridge, England).…”
Section: Corticotropin Release Studymentioning
confidence: 99%